JAHAN: A framework for procedural generation of game maps from design specifications - Amiri-Chimeh, Saeed; Haghighi, Hassan; Vahidi-Asl, Mojtaba (Entertainment computing, 2024)
Procedural content generation is a field that focuses on creating game assets employing algorithmic procedures. A critical asset in many game genres is the map. Due to the sophistication of the game map development, procedural map generation has been the subject of many studies. Considering the fundamental complexity of the game maps, many of these studies try to engage human designers in the generation process to improve the output of algorithmic procedures. However, these studies have not paid adequate attention to important non-functional requirements such as generality, comprehensiveness, controllability, and adaptability to iterative development. This paper presents a procedural map generation framework that places map designers at the center of a pipeline architecture. This framework allows designers to configure different pipeline modules and specify the characteristics of their desired map. Moreover, this framework has assertion checking features that facilitate map evaluation. We demonstrate the capabilities of this framework through one running example, along with three case studies that generate maps for first-person shooter, real-time strategy, and dungeon crawler games. Furthermore, we present a user study to show the suitability of this framework in iterative development processes and demonstrate how it reduces the labor of human designers. [Display omitted] •We presented JAHAN, a modular framework for procedural game map generation.•JAHAN is capable of generating map geometries, heightmaps, and landscapes.•We demonstrated the capabilities of JAHAN through some case studies.•We conducted a user study to investigate the benefits of JAHAN for map designers.